2015
DOI: 10.3906/sag-1311-29
|View full text |Cite
|
Sign up to set email alerts
|

The effect of total intravenous anesthesia on the postoperative cognitive functions of young and elderly patients after lumbar disk surgery

Abstract: Background/aim: The negative effects of surgery and anesthesia on cognitive functions and their relationships with many factors are well known. In the present study we aimed to investigate the effect of the total intravenous anesthesia (TIVA) method on the postoperative cognitive functions between young and elderly patients scheduled to undergo lumbar disk surgery. Materials and methods:The TIVA method was applied to 40 patients less than 65 years old (young, Group Y) and ≥65 years old (old, Group O), whose Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…This Suggests that postoperative cognitive dysfunction was temporary during TIVA with remifentanil and propofol given by TCI with or without dexmedetomidine in elderly patients undergoing ureteroscopic holmium laser lithotripsy. In contrast, İlvan G et al 19 reported that the TIVA method did not affect postoperative early cognitive functions in either old or young patients who underwent lumbar disk surgery. The time to apply the MMSE postoperatively might be responsible for the differences.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This Suggests that postoperative cognitive dysfunction was temporary during TIVA with remifentanil and propofol given by TCI with or without dexmedetomidine in elderly patients undergoing ureteroscopic holmium laser lithotripsy. In contrast, İlvan G et al 19 reported that the TIVA method did not affect postoperative early cognitive functions in either old or young patients who underwent lumbar disk surgery. The time to apply the MMSE postoperatively might be responsible for the differences.…”
Section: Discussionmentioning
confidence: 89%
“…The older surgical patients have probable cognitive impairment preoperatively, and the impairment is associated with development of delirium postoperatively 16 .We previously found that the incidence of postoperative cognitive dysfunction was higher in elderly patients with inhalational anaesthesia compared to total intravenous anaesthesia 17 . Both anesthetic and pain management strategies do appear to in uence the risk of cognitive dysfunction after elective joint arthroplasty, and perioperative pain may be a risk factor for postoperative delirium [18][19][20] . In the present study, we selected patients undergoing ureteroscopic holmium laser lithotripsy with minor acute postoperative pain, thus avoiding the effects of postoperative pain and postoperative analgesic drugs on POCD in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…[41] Total intravenous anaesthesia has shown to have a negligent effect on cognitive impairment both in young and elderly patients. [42][43][44] Inadequate post-operative pain management causes up-regulation of NMDA receptors in the hippocampal region and leads to memory decline after surgery and anaesthesia. [45] Multimodal anaesthesia and analgesic protocols, use of ultrashort-acting agents with intraoperative cerebral function monitoring should be instituted to target optimum depth of anaesthesia.…”
Section: Post-operative Dementia and Cognitive Impairmentmentioning
confidence: 99%
“…Результати інших авторів свідчать про те, що пропофол може поліпшити когнітивні функції у літніх і пацієнтів з хворобою Aль-цгеймера [22]. У дослідженні Gizem İlvan et al (2015) метод тотальної внутрішньовенної анестезії (TIVA) не впливав на когнітивні функції в ранньому післяопера-ційному періоді у старих або молодих пацієнтів, проо-перованих на поперекових дисках [23].…”
Section: літературний оглядunclassified
“…Результати інших авторів свідчать про те, що пропофол може поліпшити когнітивні функції у літніх і пацієнтів з хворобою Aль-цгеймера [22]. У дослідженні Gizem İlvan et al (2015) метод тотальної внутрішньовенної анестезії (TIVA) не впливав на когнітивні функції в ранньому післяопера-ційному періоді у старих або молодих пацієнтів, проо-перованих на поперекових дисках [23].Нейроендокринна реакція на хірургічну трав-му -це складне поєднання гормональних і метаболіч-них змін [5, 24,25]. Найбільш інформативні нейрое-ндокринні маркери стресу -швидкий підйом рівнів кортикотропін-рилізинг-фактора (КРФ), АКТГ і глю-кокортикоїдів, активізація гіпоталамічної норадренер-гічної імпульсації, що збільшує утворення глюкози в печінці і підвищений викид гіперглікемічних гормо-нів: адреналіну і глюкагону.…”
unclassified